The Role of Teachers in Building Student Character Through Regular Morning Routine Activities at SD IT Al-Ihsan Patokbeusi Subang - Aini, Nurul; Yeyeni, De; Dasuki, Ahmad Dasuki; Farihin, Ahmad; Aryani, Reva Haerunnisya (Proceeding International Conference on Religion, Science and Education, 2026)
This study aims to analyze the role of teachers in building student character through routine morning activities at SD IT Al-Ihsan Patokbeusi. This study uses a qualitative descriptive method with a field research approach. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that teachers play a significant role in shaping student character by integrating religious and moral values into daily routines. Morning activities such as reciting prayers, reading short chapters of the Qur'an, performing the dhuha prayer, and delivering brief advice (tausiyah) have proven effective in fostering discipline, responsibility, religiosity, and cooperation among students. Teachers' consistent involvement and exemplary behavior contribute to creating a positive and spiritual learning environment. Therefore, the implementation of routine morning activities not only strengthens students' spirituality but also serves as an effective strategy in character education in Islamic-based elementary schools.